2021
DOI: 10.1177/13548565211036801
|View full text |Cite
|
Sign up to set email alerts
|

Personalization and the Smart Home: questioning techno-hedonist imaginaries

Abstract: Smart home futures predicted and promoted in the discourses and practices of industry increasingly figure forms of automated decision making (ADM) into existing narratives of technological solutionism. This article interrogates how these narratives are constituted, the futures they imagine, predict and promote, and how people and households are presented within these futures. Our discussion is based on a content analysis of technology industry reports. The reports emphasize that the key to business success in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Beyond the pandemic, the implications of this research for aged care providers, policy makers or HCI designers wishing to deploy similar smart devices in older adult homes are that these technologies must be viewed as supplements -rather than replacementsto other aged care services. This aligns with smart home literature which has resisted and complicated the technological solutionism narrative that positions smart home devices as capable of independently 'taking care' of the home and its occupants [8,67,74,87]. The devices trialed in this project could enhance wellbeing outcomes for older people ageing in place, but only when provided as optional extras alongside their in-home services, which remain of high importance for the sense of community connection, social interaction and reliability.…”
Section: Provide Smart Home Technologies Forsupporting
confidence: 61%
“…Beyond the pandemic, the implications of this research for aged care providers, policy makers or HCI designers wishing to deploy similar smart devices in older adult homes are that these technologies must be viewed as supplements -rather than replacementsto other aged care services. This aligns with smart home literature which has resisted and complicated the technological solutionism narrative that positions smart home devices as capable of independently 'taking care' of the home and its occupants [8,67,74,87]. The devices trialed in this project could enhance wellbeing outcomes for older people ageing in place, but only when provided as optional extras alongside their in-home services, which remain of high importance for the sense of community connection, social interaction and reliability.…”
Section: Provide Smart Home Technologies Forsupporting
confidence: 61%
“…He argues for critical examination of conceptual foundation of researchers reasoning and decision making in design processes. There are numerous works continuing to question and disrupt accepted terms and discourses within HCI including for example Sarah Fox s work of the underlying politics on public spaces and IoT [44], Austin Toomb s investigation of commonused terms in hackerspaces [115], and various works questioning the foundations of smart home ideals and its consequences [21,75,112].…”
Section: Ideologized Relationsmentioning
confidence: 99%
“…The film's engagement with this group also critically contests problematic narratives concerning the smart home. These have been characterized by, the "new white futurism" noted above (Rottinghaus, 2021) or the "techno-hedonist" persona, which Kari Dahlgren and colleagues coined to demonstrate how dominant representations show smart home technologies as serving the gratification of masculine gendered individuals by offering pleasure, efficiency and rationalization (Dahlgren et al, 2021).…”
Section: Smart Homes For Seniorsmentioning
confidence: 99%
“…Existing research has critically revealed that technologically solutionist (Morozov, 2013) “sociotechnical imaginaries” (Jasanoff & Kim, 2015) commonly envision futures in which monetised automated technologies—such as self-driving cars or digital voice assistants—will bring about economic, environmental and public benefits. Usually based on quantitative surveys, big data analytics and deep rooted assumptions that technological advancement drives positive change, their predictive claims leave little space for the experiential realities, contingencies and serendipity of the everyday (Dahlgren et al, 2021; Strengers et al, 2021). They moreover fuel research investment in engineering, computer sciences and technology design disciplines (Pink, 2022a), where if people are accounted for they are already framed into simplified faceless roles such as those of user, consumer or citizen (Pink, Fors, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%